Molecular Implications of the PPARs in the Diabetic Eye - Andreea Ciudin; Cristina Hernández; Rafael Simó (PPAR Research)
Diabetic retinopathy (DR) remains as the leading cause of blindness among working age individuals in developed countries. Current treatments for DR (laser photocoagulation, intravitreal corticosteroids, intravitreal anti-VEGF agents, and vitreoretinal surgery) are applicable only at advanced stages of the disease and are associated with significant adverse effects. Therefore, new pharmacological treatments for the early stages of the disease are needed. Emerging evidence indicates that peroxisome proliferator-activator receptors (PPARs) agonists (in particular PPARα) are useful for the treatment of DR. However, the underlying molecular mechanisms are far from being elucidated. This paper mainly focuses on PPARs expression in the diabetic eye, its molecular implications, and the effect of PPAR agonists as a new approach for the treatment of DR. The availability of this new strategy will not only be beneficial in treating DR but may also result in a shift towards treating earlier stages of diabetic retinopathy, thus easing the burden of this devastating disease (Cheung et al. (2010)).